2015
DOI: 10.1097/bot.0000000000000346
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Follow-up in Orthopaedic Trauma

Abstract: Loss of follow-up is a common problem in orthopaedic trauma. Our study suggests different risk factors for noncompliance, including male gender, smoker, lack of commercial health insurance, and illicit drug abuse. Health care providers may consider establishing protocols for facilitating follow-up appointments to patients who are at risk for noncompliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 10 publications
5
64
4
Order By: Relevance
“…The first main finding of this study was that travel distance, BMI and HIV status were the most important predictors of attendance for follow-up visits, with an increased travel distance, increased BMI and HIV-positive status making it more likely for patients not to return for follow-up. Alcohol use, smoking and male gender have been reported as major risk factors for loss to follow-up in the literature, [4,5,8] but this was not found in the present study. Zelle et al [4] reported travel distance not to be a predictor of loss to follow-up, [4] while the present study highlights this to be a risk factor.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The first main finding of this study was that travel distance, BMI and HIV status were the most important predictors of attendance for follow-up visits, with an increased travel distance, increased BMI and HIV-positive status making it more likely for patients not to return for follow-up. Alcohol use, smoking and male gender have been reported as major risk factors for loss to follow-up in the literature, [4,5,8] but this was not found in the present study. Zelle et al [4] reported travel distance not to be a predictor of loss to follow-up, [4] while the present study highlights this to be a risk factor.…”
Section: Discussioncontrasting
confidence: 73%
“…[11] The widespread poverty in the Northern Cape means that most patients who rely on government health services also depend on the government transport system that is tasked with transporting patients across the province to their required healthcare facilities. A recent study in the USA reported that travel distance was not related to loss to follow-up, [4] but in the developing world setting of the Northern Cape, vast distances ( Fig. 2) together with poverty can potentially make returning to a hospital very challenging for patients compared with those in the developed world.…”
Section: In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The mean rate of loss to follow-up in orthopaedic trauma studies (10.5 %) was similar to that of all other subspecialty trials (10.4 %; p = 0.57). Suggested risk factors for loss to follow-up include racial and ethnic factors, age, gender, insurance status, and educational level [19][20][21][22][23]. The present investigation did not confirm age as a risk factor for loss to follow-up.…”
Section: Discussionmentioning
confidence: 94%
“…Research in trauma and orthopaedic settings from other countries has explored various factors and demographics that are associated with a higher chance of dropout in treatment and research. Common risk factors included: male gender, current smokers, younger than 30 years, high alcohol and substance use, and lack of health insurance 35,36 . Increased efforts to maintain contact with patients identified as being at higher risk of not following up, may help to decrease the possible complications resulting from unmonitored recovery 37 .…”
Section: Retentionmentioning
confidence: 99%